Eksistensi dan Kepercayaan Pemerintah Terhadap LSM Lingkungan dalam Penerapan Green Politics di Indonesia - Apriyani, Sinta (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2024)
Political activism, which cares about the environment and is embodied in the vision, mission, and programs of government and political action, must fight for the future. The form of political concern for the environment, previously referred to as environmental policy in Indonesia, has been implemented through the submission of petitions by Indonesian environmental NGOs to pay attention to ecological aspects, lawsuits over policies, and mass mobilization actions. A survey is conducted in the study. The data used to use other data to create a form of environmental and political awareness, or what is then known as